UTHM Perspective of E-Waste Disposal - Abdul Rahman, Nur Syazwina; Azlan, Alya Natasha; Badrul Hisham, Dania Qistina; Ahmad, Nor Farah Atiqah (Multidisciplinary Applied Research and Innovation, 2023)
The aim of this study is to gather people who want to recycle their e-waste through websites. To prevent toxic chemicals from polluting the environment and to bring awareness to the community about going green in order to save the life of future generations, also to get ideas from the UTHM community about innovation that can make from e-Waste. Since understanding of how to properly dispose of e-waste is still regarded as new to our society, the study method for this study is an online questionnaire via ’Google Form’ to survey knowledge about e-waste disposal among UTHM students and staff. A questionnaire is a research tool that consists of a series of questions or other forms of prompts that are used to collect data from a respondent. Responses can be compared to previous data to see whether there have been any changes in respondents’ preferences or experiences. Respondents can also choose to remain anonymous when filling out the survey. This study clearly shows that the attitude of the UTHM community towards e-waste disposal is at a good and satisfying level. Since most of the respondents in this study are students and academic staff who are involved with Environmental Engineering, the theory that they have learnt or taught has been reflected in their attitudes towards E-waste disposal. It was found that knowledge and attitudes give effect to e-waste disposal practices even at a medium level. Besides, it was discovered that while respondents in UTHM are aware of the presence of dangerous elements in e-waste, they are unfamiliar with the range and impacts on human health and the environment. However, respondents are aware that valuable metals can be found in e-waste.